2022
DOI: 10.1186/s12883-022-02803-1
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B plus fluorocytosine combined with voriconazole for the treatment of non-HIV and non-transplant-associated cryptococcal meningitis: a retrospective study

Abstract: Background Our previous study explored Amphotericin B (AMB) plus 5-flucytosine (5-FC) combined with fluconazole (FLU) therapy in the induction period, which seemed to be better than the previous AMB + 5-FC antifungal therapy in non-HIV and non-transplant-associated CM. However, based on our clinical finding, the outcomes of some CM patients who received AMB plus 5-FC combined with FLU antifungal therapy were still poor. Therefore, we need to explore new antifungal methods in non-HIV and non-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…In review of the literature, about eight literature evaluated the therapeutic efficacy of AmB combined with Voriconazole in invasive fungal infection. [1][2][3][4][5][6][7][8] Two reports are in vitro observations, 1,2 three reports are in the animal study, [3][4][5] and three reports are in patient observation. [6][7][8] The vitro observations showed combinations antifungal therapy exhibited promising results and no apparent antagonistic interaction was detected.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In review of the literature, about eight literature evaluated the therapeutic efficacy of AmB combined with Voriconazole in invasive fungal infection. [1][2][3][4][5][6][7][8] Two reports are in vitro observations, 1,2 three reports are in the animal study, [3][4][5] and three reports are in patient observation. [6][7][8] The vitro observations showed combinations antifungal therapy exhibited promising results and no apparent antagonistic interaction was detected.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Two reports are in vitro observations, 1,2 three reports are in the animal study, [3][4][5] and three reports are in patient observation. [6][7][8] The vitro observations showed combinations antifungal therapy exhibited promising results and no apparent antagonistic interaction was detected. One animal observation indicated that the efficacy of monotherapy and the two-drug combinations therapy was similar; activity was neither enhanced nor reduced with combination therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations